2020
DOI: 10.1111/codi.15242
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term survival following elective colon cancer surgery in the aged. A population‐based cohort study

Abstract: Aim The number of colorectal cancer patients increases with age. Long-term data support personalized management due to heterogeneity within the older population. This registry-and population-based study aimed to analyse long-term survival, and causes of death, after elective colon cancer surgery in the aged, focusing on patients who survived more than 3 months postoperatively. Methods The data included patients ≥ 80 years who had elective surgery for Stage I-III colon cancer in four Finnish centres. The prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
3
6
2
Order By: Relevance
“…In contrast to some previous reports [ 51 , 52 ], we found impaired long-term outcomes in elderly patients after resection for left-sided CRC. The first 3 months after surgery were suggested as the most critical for these patients [ 51 ] and the results of the present confirmed the importance of the early postoperative period as 90-days mortality reached 7.4% in elderly and only 1.6% in younger counterparts.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to some previous reports [ 51 , 52 ], we found impaired long-term outcomes in elderly patients after resection for left-sided CRC. The first 3 months after surgery were suggested as the most critical for these patients [ 51 ] and the results of the present confirmed the importance of the early postoperative period as 90-days mortality reached 7.4% in elderly and only 1.6% in younger counterparts.…”
Section: Discussioncontrasting
confidence: 99%
“…There are some limitations to this study. It was acknowledged 40 50 60 [3,35]. Future studies using these multicentre data will focus on longterm results with outcomes, and especially functional recovery.…”
Section: Discussionmentioning
confidence: 99%
“…More extensive patient data are needed to confirm the possible prognostic trends such as with CFS, ASA, MNA‐SF and GFR. Moreover, a longer follow‐up would be necessary to evaluate the complete impact of invasive cancer treatment [3,35]. Future studies using these multicentre data will focus on long‐term results with outcomes, and especially functional recovery.…”
Section: Discussionmentioning
confidence: 99%
“…However, laparoscopic surgery could not completely substitute open surgery in several circumstances, including vast tumor invasions and emergency operations. 1,[19][20][21][22][23] In fact, due to various reasons, surgeons mainly perform open surgery in our hospital. However, due to the factors such as surgical injury, organ stretch ischemia, inflammatory exudate stimulation in abdominal cavity and large incision in the abdominal wall, patients can feel moderate-to-severe pain after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Colon cancer is one of the most common malignant tumors in digestive tract, the morbidity and mortality are increasing year by year, and so far surgery remains the mainstream curative treatment for colon cancer. [1][2][3] Postoperative pain can delay the wound healing, the first ambulation and the recovery of intestinal tract, leading to the patient's body in a stress status, which results in the damage of immune function, thus promoting the recurrence and metastasis of tumor after surgery, and delaying the overall postoperative recovery speed. [4][5][6][7][8][9][10][11][12] It has been demonstrated that scientific and reasonable pain management is helpful to reduce complications and accelerate the recovery of patients.…”
Section: Introductionmentioning
confidence: 99%